2014
DOI: 10.1371/journal.pone.0085454
|View full text |Cite
|
Sign up to set email alerts
|

Paternally Expressed, Imprinted Insulin-Like Growth Factor-2 in Chorionic Villi Correlates Significantly with Birth Weight

Abstract: ContextFetal growth involves highly complex molecular pathways. IGF2 is a key paternally expressed growth hormone that is critical for in utero growth in mice. Its role in human fetal growth has remained ambiguous, as it has only been studied in term tissues. Conversely the maternally expressed growth suppressor, PHLDA2, has a significant negative correlation between its term placental expression and birth weight.ObjectiveThe aim of this study is to address the role in early gestation of expression of IGF1, IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 39 publications
7
35
1
1
Order By: Relevance
“…Such nutrient imbalance has been shown to severely impair fetal and placental development [50]. Interestingly, we found most of the disturbed gene expression were located in the KCNQ1 and IGF2/H19 clusters, consistent with the role of IGF2 as a major fetal growth regulator [54]. Diets of pregnant ewes containing different starch/fiber/protein portions have been shown to change the CpG methylation levels of specific imprinted genes such as IGF2R and H19 [20].…”
Section: Discussionsupporting
confidence: 67%
“…Such nutrient imbalance has been shown to severely impair fetal and placental development [50]. Interestingly, we found most of the disturbed gene expression were located in the KCNQ1 and IGF2/H19 clusters, consistent with the role of IGF2 as a major fetal growth regulator [54]. Diets of pregnant ewes containing different starch/fiber/protein portions have been shown to change the CpG methylation levels of specific imprinted genes such as IGF2R and H19 [20].…”
Section: Discussionsupporting
confidence: 67%
“…9 Here, we extend these studies to show that this relationship holds across the range of normal birth weight. Previous studies have reported decreased IGF2 expression in placenta from SGA pregnancies, 9,16 which may occur from early on in pregnancy, 35 and studies in mice confirm that IGF2 controls a substantial part of fetal growth. 36 These data are consistent with the predicted effects of IGF2, since paternally expressed genes augment fetal and placental development.…”
Section: Discussionmentioning
confidence: 84%
“…The authors found that increased expression of the IGF2 gene in CVS tissue was significantly associated with higher birth weight, highlighting the in utero role of IGF-2 on growth. Furthermore, 19% of infants in this study were classified as SGA and had reduced expression of IGF2 compared to appropriate for gestational age (AGA) infants [36]. …”
Section: Studies Examining Igf-2 Weight and Adipositymentioning
confidence: 99%